Contraceptive injections by community health workers in Uganda: a nonrandomized community trial - John Stanback; Anthony K Mbonye; Martha Bekiita
OBJECTIVE: To compare the safety and quality of contraceptive injections by community-based health workers with those of clinic-based nurses in a rural African setting. METHODS: A nonrandomized community trial tested provision of injectable Depo Provera (DMPA) by community reproductive health workers and compared it with routine DPMA provision at health units in Nakasongola District, Uganda. The primary outcome measures were safety, acceptability and continuation rates. FINDINGS: A total of 945 new DMPA users were recruited by community workers, clinic-based nurses and midwives. Researchers successfully followed 777 (82% follow-up): 449 community worker clients and 328 clinic-based clients. Ninety-five percent of community-worker clients were "satisfied" or "highly satisfied" with services, and 85% reported receiving information on side-effects. There were no serious injection site problems in either group. Similarly, there was no significant difference between continuation to second injection (88% among clients of community-based workers, 85% among clinic-going clients), nor were there significant differences in other measures of safety, acceptability and quality. CONCLUSION: Community-based distribution (CBD) of injectable contraceptives is now routine in some countries in Asia and Latin America, but is practically unknown in Africa, where arguably the need for this practice is greatest. This research reinforces experience from other regions suggesting that well-trained community health workers can safely provide contraceptive injections.